A Comparison of Learning Outcomes in Skills‐Based Courses: Online Versus Face‐To‐Face Formats. (April 2016) - Callister, Ronda Roberts; Love, Mary Sue
ABSTRACT: In comparing the learning outcomes of online versus face‐to‐face courses, skills‐based forms of instruction have received little attention. This study asks the question "Can skills‐based courses taught online achieve the same outcomes as face‐to‐face courses in which the instructor and students interacting in real time may have higher levels of interaction, thus potentially facilitating higher levels of skill improvement?" If so, what are the critical success factors that influence these outcomes? These questions are examined by comparing four classes in negotiations (two face‐to‐face and two online) taught by the same professor. The courses were designed to be as similar as possible except for their delivery method. Results indicate that face‐to‐face learners earned higher negotiation outcomes than online learners even when using the same technology. Suggestions are offered for improving outcomes.